Safe Food Handling Knowledge and Practices of Street Food Vendors in Polokwane Central Business District - Marutha, Khomotso J. (Foods, 2020)
Street food vending is a common business practice in most South African cities. However, street vended foods may be a source of foodborne illnesses if their handling is not well regulated and executed. This study aimed to investigate the knowledge and practices regarding food safety by street food vendors in the Polokwane central business district. This was a quantitative descriptive study where a structured questionnaire was used to collect self-reported data from street food vendors. A checklist was used to collect observed data from the vending site on vendor practices and status of the vending environment. A total of 312 vendors participated in the study, most being young females aged below 40 years (62%), single (51.2%) with less than six years of trade experience (58.3%). Although the level of knowledge was high, safe food handling practices were mostly inadequate. Most vendors operated their businesses in the open air and tents (66.2%). Vending experience significantly correlated with safe food handling practices (p < 0.05). It is significantly riskier to sell cooked rather than uncooked food in the street. Lack of resources like water and a healthy environment negatively affected food handling practices. Health promotion on food safety is recommended for street vendors.